Estudo do efeito combinado da radiólise e do processo de estiramento do Policarbonato de Bisfenol A - Oliveira, Celio Jorge Vasques de (2018)
In this work, the physical-chemical and mechanical properties of the degraded Bisphenol A polycarbonate were evaluated after exposure to gamma radiation at doses of 130 and 300 kGy. The results of the tests for the determination of the average molar weight, infrared spectroscopy (FTIR) and tensile tests, revealed that the physical-chemical and mechanical properties of the polycarbonate demonstrated significant changes in both doses, probably associated with scission of the macromolecular chains by ionizing radiation